Los espíritus de la ciencia ficción : Espiritismo, periodismo y cultura popular en las novelas de Eduardo Holmberg, Francisco Miralles y Pedro Castera - Cano, Luis C. (Book collections on Project MUSE., 2017)
"This book examines the development of Latin American science fiction from the mid-nineteenth century until the early days of Modernsmo via an in-depth discussion of the first three novels published in Spanish America: Viaje maravilloso del senor Nic-Nac al planeta Marte by Argentinian writer Eduardo Ladislao Holmberg, Desde Jupiter by the Chilean Francisco Miralles, and Querens by Pedro Castera from Mexico. These three novels incorporate all the attributes that consistently appear in a science fiction work through a blend of Darwinism and Spiritism, the two most dominant and widely-debated scientific discourses of their time. Consistent with the social and political interests in the recently independent Latin American nations, the three writers address scientific, aesthetic, intellectual and personal beliefs through a combination of utopian optimism and dystopian pragmatism."--Provided by publisher